Application of Framework in the Mobile Application of the Price Data System (Sidara) Desperindag Dumai City - Devit Satria; Mustazzihim Suhaidi (Jurnal Mantik, 2020)
The trade sector at the Dumai City Trade and Industry Office (DISPRINDAG) and also the general public need a reliable and easily accessible reference for information on food prices. This study aims to build a price data information system (SIDARA) to support price control work in the trade sector which has become a government program. The system was developed with a reference to the standard needs for monitoring food prices by the Riau Province Inflation Control Team. The system architecture utilizes RESTfull API technology, in the REST architecture, the REST server provides resources and the REST client accesses and displays these resources for further use. In designing the system, researchers use the Laravel and Ionic framework with the concept of Model View and Controller (MVC).